PENERAPAN PAJAK PENGHASILAN PADA PERUSAHAAN JOINT VENTURE (STUDI KASUS: PT. BK, PERSERO) - Maya Safira Dewi; Siti Bening Lestari (Binus Business Review, 2012)
The purpose of this writing is to determine how the implementation of policies in terms of taxation, in particular the application of income tax on the joint venture, both based on the application of tax laws and regulations, as well as based on the agreement with the contractual agreements in the Joint Venture. The method of research used in writing this thesis is descriptive method. Descriptive method used by the writer after collecting data and information gained, so it can be explained, and then to draw conclusions in a systematic, factual, and accurate information on the facts of the problem studied. The result of writing this thesis is an understanding of the application of income tax on its Joint Venture. Given this research, the reader is expected to increase knowledge about the implementation of corporate tax in the Joint Venture. In addition, the company is expected to implement the tax policy on its Joint Venture with better in the future.